Anthropology of the self : the individual in cultural perspective - Morris, Brian, 1936- (London ; Boulder, Colo. : Pluto Press, 1994)
Annotation This book looks at the 'self' in Western, Asian and African societies passing though Greek philosophy, Buddhism, Hinduism, Confuscism, Tao and African philosophy and ending with contemporary feminism. Scholarly and written in a lucid style, free of jargon, this work is written from an anthropological perspective with an interdisciplinary approach. Morris emphasises the varying conceptions of the self found cross-culturally and contrasts these with the conceptions found in the Western intellectual traditions.
1. Introduction -- 2. Greek Philosophy and Concepts of the Psyche -- 3. Buddhism and the Doctrine of No Soul (Anatta) -- 4. The Hindu Conception of the Self -- 5. Taoism, Confucianism and the Chinese Self -- 6. African Philosophy and Conceptions of the Person -- 7. People as Social Beings: Conceptions of the Person in Oceania and Melanesia -- 8. Feminist Philosophy and the Theory of the Self -- 9. Conclusions.
Includes bibliographical references (pages 199-214) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Ethnopsychology; Self (Philosophy) -- Cross-cultural studies; Individualism -- Cross-cultural studies; Self-perception -- Cross-cultural studies; Religion and culture; Self (Philosophy) -- Cross-cultural studies; Individualism -- Cross-cultural studies; Self-perception -- Cross-cultural studies; Ethnopsychology; Ethnopsychologie; Moi (Philosophie) -- Études transculturelles; Individualisme -- Études transculturelles; Perception de soi -- Études transculturelles; Religion et culture; Moi (Philosophie) -- Études transculturelles; Perception de soi -- Études transculturelles; ethnopsychology; SOCIAL SCIENCE -- Anthropology -- Cultural; Ethnopsychology; Individualism; Religion and culture; Self-perception; Self (Philosophy); Kulturvergleich; Selbst; Religion; Kultur; Ethnologie; Identitätsfindung; Cultuurpsychologie; Zelfwaarneming; Ethnopsychologie; Soi (philosophie) -- Études transculturelles; Perception de soi -- Études transculturelles; Religion et culture; Ethnopsychology; Cross-cultural studies